The dynamics of regional language attitudes as a cultural asset for sustainable tourism: A study of Balikpapan’s multilingual communities amid IKN development - Lisnawaty Simatupang; Ranti Rustika; Abdul Gafur; Tri Retno Nugroho; Febby Rio Pratama Syarif (Borneo Novelty Publishing, 2026)
Purpose - This study aims to examine the language attitudes of the Balikpapan community toward regional languages and to explore how these attitudes may influence regional identity and tourism development in the context of the new capital city (IKN) expansion. Methodology/Design/Approach - A quantitative approach was employed, collecting survey data from 384 respondents with a 5% margin of error. Multiple factors influencing language attitudes—environmental, instructional (Indonesian as the language of instruction), family, media, and institutional factors—were analyzed using significance testing to determine their predictive effects. Findings - The results show that environmental factors (Sig. = 0.000) and media/institutional factors (Sig. = 0.029) exert significant positive effects on regional language attitudes. Conversely, the use of Indonesian as a language of instruction (Sig. = 0.012) has a significant negative effect. Family influence (Sig. = 0.533), although theoretically assumed to be the strongest factor, shows no significant impact in shaping respondents’ attitudes. Overall, the Balikpapan community demonstrates attitudes toward regional languages that could be strengthened through targeted interventions such as education-based initiatives, regional language promotion, enhanced family engagement, and the creation of language-friendly public spaces. Originality/Value - This study contributes novel empirical evidence on the sociolinguistic dynamics of a rapidly developing urban area located near the emerging national capital. It highlights how regional language attitudes intersect with cultural identity and tourism development, offering practical insights for policymakers seeking to preserve linguistic heritage while promoting culturally grounded tourism in the era of IKN development.